Management effort of mottle virus by leaf extract of moringa (Moringa oleifera Lam.) and bougainvillea (Bougainvillea spectabilis Willd.) on peanut - Zulfi, Fahma Zakiya; Damayanti, Tri Asmira; Giyanto, Giyanto (Universitas Trunojoyo Madura, 2024)
Peanut mottle virus is one of peanut production constrain worldwide. It is transmitted by aphid vectors and by seeds. One of the efforts to manage viruses is by using plant extracts. This study aims to test the potency of moringa and bougainvillea leaf extract to suppress mottle virus infection in peanuts. The test consisted of four treatments: healthy control, untreated control infected by the virus, moringa, and bougainvillea leaf extracts treatment infected by the virus. The disease assessment and agronomic parameters were observed weekly. The results showed that the spray application of moringa and bougainvillea leaf extract showed lower disease incidence, significantly able to prolong the incubation period, decreased disease severity, and as well as virus titer significantly in comparison to the control. The area under the disease progress curve among leaf extract treatments was significantly different but was significantly lower in comparison to untreated control infected by the virus. The germination percentage, vigor index, and plant height were not significantly different among treated plants and control, except for the leaf numbers. In addition, the growth vigor of treated plants was better than the control. These indicate that both plant leaf extracts have antiviral activity and the ability to improve plant growth.